The influence of COVID-19 barrier measures on the positivity rate of typhoidal salmonellosis and amoebiasis in the Buea Health District, South West Region of Cameroon. - Afegenui Blaise Sunday; Raymond Babila Nyasa; Martin Mokake (Public Library of Science (PLoS), 2023)
Typhoidal salmonellosis and amoebiasis are prevalent in the Buea Health District (BHD) and it is evident that hand hygiene can reduce the transmissibility of these diseases. The barrier measures enforced by the government, in the wake of the corona virus disease 2019 (COVID-19) pandemic has led to behavioural changes which may have had an influence on the positivity rate of these diseases. This study seeks to determine the influence of COVID-19 barrier measures and the implementation of COVID-19 vaccination on the positivity rate of typhoidal salmonellosis and amoebiasis in the BHD. A retrospective study, with purposive and random sampling methods were used to select health facilities in BHD, whose laboratory records were reviewed using a data extraction form to obtain health information of patients who tested for typhoidal salmonella and/or Entamoeba histolytica from June 1, 2018 to December 31, 2021. Chi-square test was used to compare the positivity rate in the pre-and-COVID-19 and in the pre-and-vaccination era. The positivity rate of typhoidal salmonellosis and amoebiasis dropped from 57.8% and 2.7% in the pre-COVID-19 era to 34% and 1.8% in the COVID-19 era respectively, which were significant (χ2 = 945.8; P<0.001 and χ2 = 11.8; P = 0.001 respectively). Within the COVID-19 era, the positivity rate of salmonellosis and amoebiasis decreased from 39% and 2.6% before the implementation of COVID-19 vaccination to 27.7% and 0.8% respectively in the COVID-19 vaccination era and these differences were significant (χ2 = 149.1; P<0.001 and χ2 = 33.8; P<0.001 respectively). However, the positivity rate of salmonellosis between the rainy (43.5%) and the dry (42.8%) seasons and amoebiasis between the rainy (2.2%) and the dry (2%) seasons were not significantly different (χ2 = 0.6; P = 0.429 and χ2 = 0.54; P = 0.463 respectively). A significant decline in the positivity rate of typhoidal salmonellosis and amoebiasis was observed after the implementation of COVID-19 barrier measures and vaccination.